Comparison of Splatter and Aerosol Mitigation by two Suction Devices - Dr Tolulase Yemitan; Dr Adeola Ladeji; Dr Olugbenga Adenuga-Taiwo; Dr Adenike Awotile; Dr Samson Kareem (Elsevier, 2023)
Aim or Purpose: Previous studies suggested that size and shape of evacuators were important considerations to ensure aerosol and splatter reduction when using rotary instruments in dentistry, therefore this study aims to compare the aerosol and splatter mitigation by 2 suction methods in a simulated setup. Materials and Methods: Study approval was obtained from the Lagos State University Teaching Hospital Ethics Committee. In an enclosed operatory, a funnel shaped prototype 3D-printed (PROTO) evacuator tip was compared with a conventional high volume evacuator (HVE) tip in mitigating splatter and aerosol. An all-ceramic crown preparation was prepared on tooth number 46 using a diamond bur with a high-speed air-turbine for 60s, and repeated six times for each suction setup to simulate a patient under care. Quantity of splatter and aerosol generated during tooth preparation procedures with no suction as well as when both suction devices were used were measured. Comparison was by two-way analysis of variance and posthoc pairwise comparisons using a Tukey adjustment. Results: The PROTO method had statistically significant less environmental splatter (P < 0.014) and aerosol (P = 0.007) than the conventional HVE device. Both PROTO and HVE significantly reduced splatter compared to the control with no suction, however, no significant difference was observed in the amount of aerosol when compared with the control trials. Conclusions: These results showed that both devices mitigated splatter better than aerosol. It therefore provide evidence for adjunctive means of reducing risk of direct transmission of infection in the dental practice by combining strategies of protective procedures, improved room ventilation and use of air filtration system.